Fenomena dan Dampak Budaya Kerja ‘996’ di Cina - Pemahanan Lintas Budaya - Sutomo, Nur Fatimah (PT. Alahyan Publisher Sukabumi, 2023)
China is a country that has rapidly made a movement in the areas of technology, entertainment, and many others. Tech companies have become everyone's favorites to get a job. However, in 2018, a new workplace culture emerged known as '996'. ‘996’ is a term to explain that the employee has to work from 9 a.m. to 9 p.m. in six days of a week. This kind of culture has been known on social media since people started to protest through an app called Bighit and release a list of companies that apply the work culture of ‘996’. This culture had attention from the government; in the government law of the China Republic, it was never written the same regulation as ‘996’, and ‘996’ has broken the rules of the regulation on working hours that should be obligated. ‘996’ creates different perspectives among people; some of them are taking it as a normal thing, while some people raise their voice against ‘996’ that has many negative impacts on the physical and mental conditions of the employees. This journal has the goal of giving knowledge and understanding about cross-cultural understanding to the reader. This journal uses the qualitative method for analysis.